Production of bacterial cellulose from glycerol: the current state and perspectives - Zikmanis, Peteris; Kolesovs, Sergejs; Ruklisha, Maija; Semjonovs, Pavels (Bioresources and bioprocessing, 2021)
Current research in industrial microbiology and biotechnology focuses on the production of biodegradable microbial polymers as an environmentally friendly alternative to the still dominant fossil hydrocarbon-based plastics. Bacterial cellulose (BC) is important among microbial polymers due to its valuable properties and broad applications in variety of fields from medical to industrial technologies. However, the increase in BC production and its wider deployment is still limited by high costs of traditionally used raw materials. It is therefore necessary to focus on less expensive inputs, such as agricultural and industrial by-products or waste including the more extended use of glycerol. It is the environmentally harmful by-product of biofuel production and reducing it will also reduce the risk of environmental pollution. The experimental data obtained so far confirm that glycerol can be used as the renewable carbon source to produce BC through more efficient and environmentally friendly bioprocesses. This review summarizes current knowledge on the use of glycerol for the production of commercially prospective BC, including information on producer cultures, fermentation modes and methods used, nutrient medium composition, cultivation conditions, and bioprocess productivity. Data on the use of some related sugar alcohols, such as mannitol, arabitol, xylitol, for the microbial synthesis of cellulose are also considered, as well as the main methods and applications of glycerol pre-treatment briefly described.